(untitled) (Journal of history, 2023)
The aim of the article is to examine the general characteristics and main features of the Botai-Tersek historical and cultural community based on archaeological materials through the application of historical-comparative analysis. The authors compare the lifting materials from the "pure" Tersek sites of Kumkeshu-1, Kozhay-1, and the Botai settlements - Botai, Krasny Yar. Comparative analysis reveals similarities between archaeological findings in terms of raw material production, processing techniques, ceramic ornamentation, and unique artifacts. The materials from the Kumkeshu-1 and Kozhay-1 settlements, summer Tersek settlements, are of particular interest for comparative analysis. In the historiography of archaeology, there has long been a debate about the Botai and Tersek cultures. The scientific discussion between archaeologists V.N. Logvin, S.S. Kalieva, and V.F. Zaibert led to the division of one archaeological culture into two separate cultures that coexisted at the same time. In recent years, the majority of specialists in this field tend to consider them as one culture, even a historical-cultural community. The Botai-Tersek historical-cultural community covered the territory of Northern Kazakhstan in the 4th millennium BCE and is characterized by the earliest evidence of horse domestication. The application of interdisciplinary research and modern methodology will further reveal opportunities to unite them as a whole. The results obtained from past field seasons show similarities between various objects as well as the spiritual and material culture of ancient inhabitants of the northern regions. Currently, the obtained materials based on the correlation of key multilayered sites of the two archaeological cultures allow for the specification of the main periods of regional cultures, clarification of common features, synchronization of general characteristics, exploration of historical parallels and identification of the cultural-economic type of the Botai-Tersek people. Keywords: Botai-тersek culture, Kumkeshu-1, Kozhay-1, summer settlements, Chalcolithic, Botai, Krasnyі Yar, stone industry.